Observational challenges in Lyα intensity mapping. Issue 3 (7th September 2016) - Comaschi, P.; Yue, B.; Ferrara, A.
Abstract : Intensity mapping (IM) is sensitive to the cumulative line emission of galaxies. As such, it represents a promising technique for statistical studies of galaxies fainter than the limiting magnitude of traditional galaxy surveys. The strong hydrogen Lyα line is the primary target for such an experiment, as its intensity is linked to star formation activity and the physical state of the interstellar and intergalactic medium. However, to extract the meaningful information, one has to solve the confusion problems caused by interloping lines from foreground galaxies. We discuss here the challenges for a Lyα IM experiment targeting z > 4 sources. We find that the Lyα power spectrum can be, in principle, easily (marginally) obtained with a 40 cm space telescope in a few days of observing time up to z ≲ 8 ( z ∼ 10) assuming that the interloping lines (e.g. Hα, [O ii ], [O iii ] lines) can be efficiently removed. We show that interlopers can be removed by using an ancillary photometric galaxy survey with limiting AB mag ∼26 in the near-infrared bands ( Y, J, H, or K ). This would enable detection of the Lyα signal from 5 < z < 9 faint sources. However, if a [C ii ] IM experiment is feasible, by cross-correlating the Lyα with the [C ii ] signal, the required depth of the galaxy survey can be decreased to AB mag ∼24. This would bring the detection at the reach of future facilities working in close synergy.